(untitled) (Italian Review of Legal History, 2021)
The aim is to trace a line of evolution of the notarial profession through the centuries from the late Middle Ages to the contemporary age in central-northern Italy between rise and decline, two poles of a multiform development. In the reconstruction, attention will be focused on some moments and junctions: the notary of the late medieval age intervenes in society and in institutions with a growing role, aware of his function and strong in his preparation, verified upon entering the business. The sixteenth century seems to be a moment of crisis, at least in the widespread perception in society. Preparation checks are intensified, archives are established, the ‘nobility’ of notaries is discussed. Between the end of the eighteenth and nineteenth centuries, state interventions multiplied up to the first unitary laws: only in 1913 a degree was required as a requirement for the profession.